(untitled) (Educational Dimension, 2022)
The study focuses on one of the mobile-oriented environment competence components for software engineering (SE) students. It has been demonstrated that the implementation of the higher education standard for SE bachelors has generated a number of issues in terms of ensuring training quality, principally due to a lack of specification for both skills and learning outcomes. Designing a precise framework of professional competencies for SE bachelors is one method to overcome these issues. The research examines methods for developing K14 (the ability to participate in software design, including modeling (formal description) of its structure, behavior, and working processes), a critical particular professional competency for future software engineers. Recommendations for software design teaching techniques, learning content, modeling and design tools, and assessment of the level of formation of relevant competence are developed based on a historical and genetic review of software design training among SE students in the UK, USA, Canada, Australia, New Zealand, and Singapore. The industrial-style software design training (studio training) is used as an example. The transition from architectural to detailed design, as well as project implementation, are discussed. The study’s future prospects include substantiating the third engineering component of SE – software construction (after requirements engineering and design engineering).